The Influence of Sesquiterpenes from Myrica rubra on the Antiproliferative and Pro-Oxidative Effects of Doxorubicin and Its Accumulation in Cancer Cells - Ambrož, Martin (Molecules, 2015)
The sesquiterpenes β-caryophyllene, β-caryophyllene oxide (CAO), α-humulene (HUM), trans-nerolidol (NER), and valencene (VAL) are substantial components of the essential oil from Myrica rubra leaves which has exhibited significant antiproliferative effects in several intestinal cancer cell lines, with CaCo-2 cells being the most sensitive. The present study was designed to evaluate the effects of these sesquiterpenes on the efficacy and toxicity of the anticancer drug doxorubicin (DOX) in CaCo-2 cancer cells and in primary culture of rat hepatocytes. Our results showed that HUM, NER, VAL and CAO inhibited proliferation of CaCo-2 cancer cells but they did not affect the viability of hepatocytes. CAO, NER and VAL synergistically potentiated the efficacy of DOX in cancer cells killing. All sesquiterpenes exhibited the ability to selectively increase DOX accumulation in cancer cells and did not affect DOX concentration in hepatocytes. Additionally, CAO and VAL were able to increase the pro-oxidative effect of DOX in CaCo-2 cells. Moreover, CAO mildly ameliorated DOX toxicity in hepatocytes. Based on all results, CAO seems to be the most promising compound for further testing.